Visual Contemporary Painting Based on The Visual Appropriation of Abhimanyu’s Death - Bayutha, Ida Bagus Rekha; Karja, I Wayan; Mudana, I Wayan (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2024)
The concept of visual appropriation involves using elements borrowed from others to create a work of art. In this research, appropriation entails utilizing images and narrative context from various sources to depict Abhimanyu’s death on the 13th day of the Bharatayuda war. This article explains the method for creating the visual appropriation of Abhimanyu. The process of creating visual appropriation is based on exploring, designing, and realizing craft arts, incorporating digital sketching, manipulation, media and technique discovery, imprimatura, collage, cropping, coloring, and finishing. The creation process involves identifying visual forms and their relationship to current phenomena and adding new meanings that alter the original context. The aim of creating contemporary painting is to make young people aware of the challenges or obstacles of the current situation and the need to develop strategies to deal with them. Resulting works aim to juxtapose visual references to provoke thought and reinterpretation of their meaning for the audience.